PERAN COMMON MARKET AMERIKA LATIN/ MERCADO COMÚN DEL SUR (MERCOSUR) DALAM MENINGKATKAN PEROKOMIAN BRASIL MELALUI KERJASAMA EKONOMI - Siti Azizah; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study will be describe the function and role of MERCOSUR (Mercado Comun del Sur) as a regional organization in Latin America in Brazil in improving the economy through economic cooperation. The majority of the regional integration projects are first and foremost economic processes. They are based on the political will of elites and on political decisions on the part of governments and powerful economic agents. MERCOSUR is a regional integration initiative that includes Argentina, Brazil, Paraguay and Uruguay as current members, with negotiations towards including also Chile and Bolivia.This research show that MERCOSUR can bring positive benefits for Brazil’s economic, politics, social and culture sector. The aim is twofold: on the one hand, to assess whether regional integration policies have diffused to the domestic policy arena, generating policy impacts and institutional changes in the member States; on the other, to evaluate the possible impact of higher education regulatory regionalism prompted by the European Union on MERCOSUR´s policies.As for the methode used in the study is qualitative research. The data obtained from literature in the form of books, documents, journals, newspapers, internet and other media that related to the issues.Key word: free trade areas, common market, export-import, investment, Gross Domestic Bruto (GDP)